(untitled) (LIS TODAY, 2024)
The study investigates the use and awareness of e-resources among postgraduate students in the Faculty of Social Sciences at Barkatullah University, Bhopal. E-resources, such as online journals, databases, and digital libraries, have become increasingly important in academic research and learning. This paper aims to assess the level of awareness, access, and utilization of e-resources by postgraduate students, as well as identify the barriers and challenges they face. The study employed a survey-based methodology, involving a structured questionnaire distributed to a sample of 110 postgraduate students across various departments within the Faculty of Social Sciences. The findings reveal a moderate level of awareness and utilization of e-resources among the respondents.